Pencegahan Bornout Syndrome dengan Metode Terapi Sufistik Illaj Qudsi (TSIQ) Sa`id Nursi Pada Kelompok Karyawan “Aria Statinonary” Kecamatan Siman Kabupaten Ponorogo Jawa Timur; Metode Community-Based Participatory Research (CBPR) - Mudin, Moh. Isom; Hasib Amrullah; Neneng Uswatun Hasanah (Wisanggeni: Jurnal Pengabdian Masyarakat, 2024)
A community service program was conducted in partnership with Toko Aria Stasinary Ponorogo. A situational analysis revealed that approximately 60% of employees were at risk of burnout due to high work pressure, negatively impacting their mental health and productivity. Additionally, spiritual support facilities, such as places of worship and spiritual reading materials, were underutilized. The program employed a Community-Based Participatory Research (CBPR) approach, involving a series of steps including foundation laying, planning, data gathering and analysis, and action planning. Activities encompassed burnout syndrome education, and spiritual guidance based on the Sufiistic Illaj Qudsi Nursi Therapy (TSIQN), which involved elements such as tauhid suggestion, focused prayer, and tasbihat. Furthermore, improvements were made to the worship facilities, and technological resources such as the Muthala'ah Risale-i Nur application, electronic books, and focused prayer guides were provided. The results indicated that each therapy component, including tauhid suggestion, focused prayer, and tasbihat, contributed to stress reduction, improved focus, and a deeper sense of purpose in work. Employee mental health improved by 95%, and there was a notable increase in employees' understanding of tauhid values, a more positive attitude, and enhanced productivity.